Bromodomain AAA+ ATPases get into shape. Issue 1 (1st January 2020) - Murawska, Magdalena; Ladurner, Andreas G.
ABSTRACT: Bromodomain AAA+ ATPases (A TPases a ssociated with diverse cellular a ctivities) are emerging as oncogenic proteins and compelling targets for anticancer therapies. However, structural and biochemical insight into these machines is missing. A recent study by Cho et al . reports the first cryo-EM structure of a bromodomain AAA+ ATPase and provides first insights into the functions of this putative histone chaperone.